Impact of Part-Time Teachers on Secondary Schools of Kisoro District: A Case Study of Kisoro Municipality. - Arinda, Emilly (Kabale University, 2024)
Many institutions, secondary schools, and other places of learning, lectures, teachers, and tutors use the trick of par timing in places of their work that is; teaching from more than one school, universities, and other institutions of learning. This has a great impact on the education of the learners. The purpose of the study is to find out the impact of part-time teachers on secondary schools' of Kisoro district, a case study of Kisoro Municipality